2019
DOI: 10.1038/s41598-019-39553-z
|View full text |Cite
|
Sign up to set email alerts
|

Cancer associated fibroblasts sculpt tumour microenvironment by recruiting monocytes and inducing immunosuppressive PD-1+ TAMs

Abstract: Fibroblasts turn into cancer associated fibroblasts (CAFs) in the tumour microenvironment. CAFs have recently attracted attention for their function as a regulator of immune cell recruitment and function in addition to their tumour-promoting roles. In this study, we aimed to determine the role of CAFs on monocyte recruitment and macrophage polarization in breast cancer. CAFs, which were α-SMA expressing fibroblasts in contrast to normal fibroblasts (NFs), effectively recruited monocytes. Recruitment of monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
210
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(217 citation statements)
references
References 56 publications
7
210
0
Order By: Relevance
“…Similar to their role in normal wound healing process, in the context of cancer, CAFs interaction with tumor cells occurs at several interfaces. CAFs produce ECM proteins, which prompts immunosuppression of tumor cells by recruiting immunosuppressive cells [64,65] such as monocytes and inducing immunosuppressive PD-1+ TAMs, as recently shown in breast cancer cells in vitro [66]. In addition, CAFs promote angiogenesis by producing fibroblast growth factor 2 (FGF2), and vascular endothelial growth factor A (VEGFA) in different cancers [67] as well as galectin-1 expression in gastric cancer [68].…”
Section: Cancer-associated Fibroblast (Cafs)mentioning
confidence: 84%
“…Similar to their role in normal wound healing process, in the context of cancer, CAFs interaction with tumor cells occurs at several interfaces. CAFs produce ECM proteins, which prompts immunosuppression of tumor cells by recruiting immunosuppressive cells [64,65] such as monocytes and inducing immunosuppressive PD-1+ TAMs, as recently shown in breast cancer cells in vitro [66]. In addition, CAFs promote angiogenesis by producing fibroblast growth factor 2 (FGF2), and vascular endothelial growth factor A (VEGFA) in different cancers [67] as well as galectin-1 expression in gastric cancer [68].…”
Section: Cancer-associated Fibroblast (Cafs)mentioning
confidence: 84%
“…51 Gok et al reported that compared to NFs, CAFs F I G U R E 2 Markers of CAFs could not only recruit monocytes via monocyte chemotactic protein-1 (MCP-1) and stromal cell-derived factor-1 (SDF-1), but also differentiated monocytes into M2 macrophages with higher expression of IL-10, therefore exerting immunosuppressive roles in breast cancer. 52 In prostate cancer, CAFs are beneficial factors for monocyte recruitment to cancer cells, mainly by transferring stromal derived growth factor-1 and promoting the transformation of macrophages into the M2 phenotype. 53 This complex interaction between tumour cells, CAFs and M2 macrophages enhances the motility of tumour cells, thereby promoting escape from primary tumours, metastatic diffusion and the angiogenesis of endothelial cells.…”
Section: Interaction Between Cancer-associated Fibroblasts and Macrmentioning
confidence: 99%
“…turn enemies into allies. Mirroring real-life global diplomacy, the re-educating of cancer cells, CAFs, CAMs, and CANs have been proposed as a way to treat cancer (Gok Yavuz et al, 2019;Shen et al, 2016). Controlling the composition of the ECM is another possible strategy (Senthebane et al, 2018).…”
Section: Cancer As a Metaphormentioning
confidence: 99%